2023
DOI: 10.1108/ijse-03-2023-0239
|View full text |Cite
|
Sign up to set email alerts
|

What do individuals know, feel and do from a financial perspective? An empirical study on financial satisfaction

Jitender Kumar,
Manju Rani,
Garima Rani
et al.

Abstract: PurposeFinancial satisfaction is a potential ambition of individuals' lives that requires well-strategized economic behaviors. The authors examine the impact of various factors on the financial behavior (FB) and financial satisfaction (FIS) of individuals in India's National Capital Region (NCR).Design/methodology/approachThrough a literature review, a survey questionnaire was formulated using existing scales on FIS. For more in-depth insights, data are obtained from 427 respondents in the NCR region using sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…These results suggest that the study is not significantly affected by common method variance, as confirmed by the findings of Kumar et al. (2024a, b, c).…”
Section: Methodssupporting
confidence: 77%
“…These results suggest that the study is not significantly affected by common method variance, as confirmed by the findings of Kumar et al. (2024a, b, c).…”
Section: Methodssupporting
confidence: 77%
“…Hair et al (2019) state that the CA and composite reliability (CR) values lie between 0.7 and 0.95. In Table 2, the values of CA (0.717-0.878) and CR (0.750-0.917) lie between the recommended value and confirmed data validity and reliability (Kumar et al, 2023a(Kumar et al, , 2023b.…”
Section: Assessment Of Measurement Modelmentioning
confidence: 57%
“…For this purpose, the authors measured multicollinearity through the “variance inflation factor (VIF)”. The expert advised that when the VIF value is less than 5, indicating no multicollinearity issue between the latent constructs (Kumar et al , 2023a). The authors observed that the VIF value in this research is less than the suggested cut-off value (refer to Table 4) and confirms the robustness of the model (Shehzad et al , 2022).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%